DUAL THREE-PHASE ADJUSTABLE SPEED DRIVE WITH SYNCHRONIZED SPACE-VECTOR MODULATION - Oleschuk V.I.; Prudeak R.; Sizov A.S.; Iaroshenco E.M. (Problems of the Regional Energetics)
Split-phase symmetrical motor drive on the base of two voltage source inverters, controlled by algorithms of synchronized pulse width modulation (PWM), has been investigated. Simulation results are presented for dual three-phase power conversion systems with continuous, discontinuous and combined versions of synchronized PWM.